Visualizing the invisible: inner plexiform layer stratification with conventional spectral-domain optical coherence tomography. - Guerra, Ricardo Luz.; Roisman, Luiz.; Duker, Jay S; Querques, Giuseppe.; Lucatto, Luiz Filipe.; Badaró, Emmerson.; Barbosa, Gabriel Castilho.; Novais, Eduardo Amorim. (Tufts University. Tisch Library., 2025)
Keywords: Inner plexiform layer, Optical coherence tomography, Spectral-domain, Retinal imaging.; Springer Open.